GENDER REPRESENTATION IN THE ENGLISH TEXTBOOK ENTITLED “PATHWAY TO ENGLISH FOR SMA/MA GRADE X” - Alvia Nurrahma Ekasiwi; Ouda Teda Ena (Eltin Journal : Journal of English Language Teaching in Indonesia, 2022)
Understanding gender equality is crucial in education to reduce sexual bias and sexual violence. As the textbook is one of the most important teaching tools in ELT, it is important to represent the issues of gender equality. The representation of gender, however, needs to be planned carefully in order to avoid gender bias. This present study aims to analyze whether gender was represented equally or not in one of the Indonesian English textbooks. This research applied content analysis and critical discourse analysis. The data source of this research was taken from “Pathway to English for SMA/MA grade X’. The data then was analyzed based on the eight-factors procedures as proposed by Amerian and Esmaili (2015). It was revealed that the textbook did not fairly present both genders. The representations of men in the contents of the textbook were found to be higher in numbers than the representations of women. Based on the findings, it is suggested that English book writers need to be more careful in using any content related to gender. They need to present both genders equally in order to promote awareness of gender equality.